Administration of intravenous morphine for acute pain in the emergency department inflicts an economic burden in Europe - Montserrat Casamayor; Karen DiDonato; Marc Hennebert; Luca Brazzi; Gregor Prosen (BioExcel Publishing Ltd, 2018)
Background: Acute pain is among the leading causes of referral to the emergency department (ED) in industrialized countries. Its management mainly depends on intensity. Moderateto- severe pain is treated with intravenous (IV) administered opioids, of which morphine is the most commonly used in the ED. We have estimated the burden of IV administration of morphine in the five key European countries (EU5) using a micro-costing approach. Scope: A structured literature review was conducted to identify clinical guidelines for acute pain management in EU5 and clinical studies conducted in the ED setting. The data identified in this literature review constituted the source for all model input parameters, which were clustered as analgesic (morphine), material used for IV morphine administration, nurse workforce time and management of morphine-related adverse events and IV-related complications. Findings: The cost per patient of IV morphine administration in the ED ranges between €18.31 in Spain and €28.38 in Germany. If costs associated with the management of morphine-related adverse events and IV-related complications are also considered, the total costs amount to €121.13-€132.43. The main driver of those total costs is the management of IV-related complications (phlebitis, extravasation and IV prescription errors; 73% of all costs) followed by workforce time (14%). Conclusions: IV morphine provides effective pain relief in the ED, but the costs associated with the IV administration inflict an economic burden on the respective national health services in EU5. An equally rapid-onset and efficacious analgesic that does not require IV administration could reduce this burden.